Optimisation of electroplating parameters and surface defect analysis / Logapriya Logamaintan - Logapriya, Logamaintan (2019)
Silver is a well-established metal used for coatings in various industries mainly in surface finishing of jewelries and decorative items. The coatings deposited on surface of substrate has to be smooth and even to ensure the coating deposited serves its purpose. There are various electroplating parameters that affect the surface roughness and surface defects of electroplated substrates. Therefore, this research is aimed to obtain the optimum parameters namely current density and plating time of silver cyanide electroplating process for bonded porcelain items produced in Royal Selangor. The optimisation was done by varying the current density and plating time using the Taguchi model to obtain the range of parameters for this study. The plated substrates were evaluated for surface roughness, coating thickness and adhesiveness accordingly. From the analysis done, as the current density and plating time increases, the surface roughness of the substrate surface increases due to increasing nucleation rate. This can be correlated with the surface roughness result and coating thickness images obtained from SEM whereby the coating thickness was also found to increase along with the increasing current density and plating time. Based on the results obtained from this study, it was found that the optimum current density was at 4A and plating time of 3 hours for the silver cyanide electroplating bath in Royal Selangor International.